Skeletal maturation, body size, and motor coordination in youth 11-14 years - Freitas, Duarte Luís (2018)
Purpose: The objective of this study is to estimate the relative contribution of biological maturation to variance in the motor coordination (MC) among youth and to explore gender differences in the associations. Methods: Skeletal maturation (Tanner-Whitehouse 3), stature, body mass, and MC (Ko¨rperkoordinationstest fu¨rKinder) were assessed in 613 youths, 284 boys and 329 girls 11–14 yr of age. Standardized residuals of skeletal age on chronological age were used as the estimate of skeletal maturity status independent of chronological age. Hierarchical multiple regression analyses were used to analyse associations between skeletal maturity status and MC. Results: Skeletal maturity status by itself, i.e., standardized residuals of skeletal age on chronological age (step 3) explained a maximum of 8.1% of the variance in MC in boys ($R32 in the range of 0.0%–8.1%) and 2.8% of the variance in girls ($R32 in the range of 0.0%–2.8%), after controlling for stature, body mass and interactions of the standardized residuals of skeletal age on chronological age with stature and body mass. Corresponding percentages for the interactions of the standardized residuals of skeletal age and stature and body mass, after adjusting for stature and body mass (step 2) were 8.7% in boys ($R22 in the range of 0.3%–8.7%) and 7.1% in girls ($R22 in the range of 0.1%–7.1%). Chow tests suggested structural changes in A-coefficients in the four MC tests among boys and girls, 12–13 yr. Conclusion: The percentage of variance in the four MC tests explained by skeletal maturation was relatively small, but the relationships differed between boys and girls. By inference, other factors, e.g., neuromuscular maturation, specific instruction and practice, sport participation, and others may influence MC at these ages.